2004
DOI: 10.1016/j.febslet.2004.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The salt bridge of calcineurin is important for transferring the effect of CNB binding to CNA

Abstract: Calcineurin (CN) is a heterodimer consisting of a catalytic subunit (CNA) and a regulatory subunit (CNB). The crystal structure shows that three residues or regions of CNA are mainly responsible for the interaction with CNB: the CNB binding helix (BBH), the N-terminus, and Glu53 that forms a salt bridge with Lys134 of CNB. In this report, we try to find the role that the salt bridge plays in the interaction between CNA and CNB. We found that mutation of Glu53 greatly reduced its responsiveness to CNB in the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It is known that both CnB and Ca 2 þ /CaM are important to activate phosphatase activity of CaN (Klee et al, 1988), but here we found that CaM could compete for the binding of c-Jun to CaN (Figure 3b). According to previous report, CnB alone, but not CaM, is able to activate the phosphatase activity of CaN by about 10-fold, and synergistic activation can be observed when CnA interacts with both CnB and Ca 2 þ /CaM (Hou et al, 2004). Therefore, we speculate that CnB may compensate for the partial loss of CaN activity as a result of the competitive binding between CaM and c-Jun to CaN.…”
Section: Discussionmentioning
confidence: 95%
“…It is known that both CnB and Ca 2 þ /CaM are important to activate phosphatase activity of CaN (Klee et al, 1988), but here we found that CaM could compete for the binding of c-Jun to CaN (Figure 3b). According to previous report, CnB alone, but not CaM, is able to activate the phosphatase activity of CaN by about 10-fold, and synergistic activation can be observed when CnA interacts with both CnB and Ca 2 þ /CaM (Hou et al, 2004). Therefore, we speculate that CnB may compensate for the partial loss of CaN activity as a result of the competitive binding between CaM and c-Jun to CaN.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, the crystal structure revealed considerable contacts of the CaN R N-terminus with Ca 2+ binding motif 3 of the B subunit, suggesting a role in CaNB binding and thus regulation of phosphatase activity. Additionally, it was proposed that the formation of a salt bridge between Glu53 of CaNA R and Lys134 of CaNB contributes to a conformational change in the catalytic subunit leading to the activation of CaN (53). The loss of phosphatase activity after proteolytic removal of the CaN R N-terminus also suggests an involvement in the regulation of the active site (19).…”
Section: Discussionmentioning
confidence: 99%
“…Research also shows that BBH and the N-terminus are mainly responsible for the interaction with CNB. Work in our laboratory has also shown that a salt bridge between Glu53 and Lys134 plays an important role in stabilizing the dimeric structure [25] . The CBD contains an amphipathic helix that interacts with the hydrophobic region of CaM.…”
Section: Figurementioning
confidence: 97%